Biological effectiveness of imidacloprid on the Asian citrus psyllid - Cortez-Mondaca, Edgardo; Pérez-Márquez, Jesús; Ángel-López, Miguel Ángel; Valenzuela-Escoboza, Fernando Alberto (Revista Mexicana de Ciencias Agrícolas, 2025)
Diaphorina citri Kuwayama, better known as the Asian citrus psyllid, is the main pest of the Persian lime due to the direct and indirect damage it causes and, currently, there are not enough chemical insecticides for its control in the field. Therefore, this work aimed to determine the biological effectiveness of 12 successive applications of imidacloprid at 25-day intervals on immature Asian citrus psyllid individuals in a Persian lime grove in order to define whether the effectiveness of the pesticide decreases as a function of the number of sprays. Before applying the insecticide, 18 tender shoots were sampled and 72 h after application, the number of live immature D. citri individuals was counted. A completely randomized design was used and mortality data were subjected to an analysis of variance. The biological effectiveness of imidacloprid on D. citri was high (up to 90%) during the first successive applications, then mortality on eggs declined by 10% in the sixth application, whereas in the tenth, it decreased significantly by more than 30%. In small nymphs, the reduction in mortality was 10% from the seventh application and in the tenth, it was significantly lower (17%). In large nymphs, the reduction in mortality was 10% in the seventh application while in the eleventh, it significantly declined (18%). In conclusion, the biological effectiveness of imidacloprid decreased after several successive applications on immature D. citri individuals.
Keywords: Chemical control; insecticide; mortality